Dynamics of Team Reflexivity after Feedback - Gabelica, Catherine; Van den Bossche, Piet; Segers, Mien; Gijselaers, Wim (Frontline Learning Research, 2014)
A great deal of work has been generated on feedback in teams and has shown that giving performance feedback to teams is not sufficient to improve performance. To achieve the potential of feedback, it its stated that teams need to proactively process this feedback and thus collectively evaluate their performance and strategies, look for alternatives, and make clear decisions about ways to tackle their task. This concept of team reflexivity has been commonly described as a sequence of behaviours, which relative importance has not been demonstrated. Further, empirical research investigating the dynamic aspects of reflexivity has been scarce. This study sought to explore how reflexivity evolves over time and at which moments of the team interaction it is related to team performance. Thirty-two student dyads participated to a cognitively complex task (flight simulation) over four performance episodes comprising action phases followed by transition (feedback) phases. High interdependence between participants (pilots and co-pilots) was ensured through the distribution of complementary knowledge in the dyads. The results showed that teams seldom engaged in full cycles of reflective behaviours. When looking into individual behaviours, teams exhibited more reflective behaviours during action over time, while their reflective behaviours during feedback did not change, demonstrating a suboptimal feedback processing as time goes by. Additionally, it was demonstrated that teams were capable to learn from their past and act upon feedback to better subsequent team performance but also that initial performance acts as a trigger to future reflective behaviours.